Resilience and Adaptation Indicators to The Challenges of War Among Educators in the Kherson Region - Pinchuk, Оlena (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2025)
This article presents the results of a study on stress coping resources within the educational community working under conditions of heightened psychological tension in the frontline zone. The relevance of the study is driven by the necessity to understand the adaptation mechanisms and support the psychological well-being of educators who daily face the consequences of military actions. The aim of the study was to identify the most sought-after types of stress coping resources (cognitive, emotional, social, physical, spiritual/philosophical) and to analyze their relationship with the emotional state of educators. The study involved educators working in the frontline zone. Data collection was conducted using a questionnaire that included statements aimed at assessing the frequency of using various stress coping strategies on a 10-point scale. The results of the study revealed that the most frequently used stress coping resources among educators are cognitive strategies related to problem analysis and the search for their solutions, as well as spiritual and philosophical attitudes that support belief in  own strengths and positive thinking. Physical activity also plays a significant role in coping with stress. Correlation analysis showed the presence of statistically significant positive relationships between emotional state and most of the studied resources. Particularly moderate correlations were found with positive thinking (r = +0.43), understanding own inner world (r = +0.44), goal-orientedness (r = +0.389), and the strongest positive relationship was observed with the habit of taking care of himself and his health (r = +0.523). The findings underscore the importance of a comprehensive approach to supporting the psychological well-being of educators working in the challenging conditions of the frontline zone. Strengthening cognitive problem-solving skills, supporting a positive outlook, encouraging physical activity, and fostering the habit of self-care are key directions for psychological assistance and resilience support for educators. Further research may focus on exploring the specific mechanisms of the influence of various resources on emotional state and developing effective interventions for this vulnerable professional group.